2017
DOI: 10.1186/s12871-017-0326-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the myocardial protective effect of sevoflurane versus propofol in patients undergoing heart valve replacement surgery with cardiopulmonary bypass

Abstract: BackgroundThis study aimed to compare myocardial protective effects of anaesthesia with intravenous infusion of propofol versus inhalation of sevoflurane in patients undergoing heart valve replacement surgery with cardiopulmonary bypass.MethodsSeventy-six patients undergoing valve replacement with cardiopulmonary bypass were randomly assigned to propofol or sevoflurane anesthesia during the surgery, respectively. For assessing myocardial injury, cardiac troponin I (cTnI) and creatine kinase isozyme (CK-MB) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Several studies have shown the beneficial effects of volatile anaesthetics relative to propofol during cardiac surgery 19 , 20 , indexed by lower creatine kinase-MB (CK-MB) levels with volatile anaesthetics compared to propofol-based anaesthesia. However, cardiac enzymes do not guarantee immune status during OHS since they are associated only with myocardial injury related to surgical trauma 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the beneficial effects of volatile anaesthetics relative to propofol during cardiac surgery 19 , 20 , indexed by lower creatine kinase-MB (CK-MB) levels with volatile anaesthetics compared to propofol-based anaesthesia. However, cardiac enzymes do not guarantee immune status during OHS since they are associated only with myocardial injury related to surgical trauma 21 .…”
Section: Discussionmentioning
confidence: 99%
“…At clinically relevant concentrations, the incidence of arrhythmia is relatively low, but the effect of arrhythmia inhibition is more signi cant. Studies have demonstrated that propofol has a protective effect on myocardial ischemia and arrhythmia which are caused by ischemia-reperfusion injury [11][12] . Propofol also has been shown to terminate atrial brillation and VT storm [13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, sevo urane may also affect the induction of VT, which mainly produces a cascade reaction through a variety of signal transduction pathways such as protein kinase C, tyrosine protein kinase, etc., changing the gene expression of cardiomyocytes, and producing a variety of anti-injury factors. Furthermore, sevo urane also prevents intracellular calcium overload through KATP channels, reduces ischemia-reperfusion injury and produces cellular protection [12] , so as to decrease the occurrence of ventricular arrhythmias. In addition, sevo urane and other volatile anesthetics can also delay atrioventricular repolarization and reduce the possibility of inducing ventricular arrhythmia in vitro by prolonging the duration of the action potential, but its clinical signi cance is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Volatile anesthetic agents have the potential to provide myocardial protection by anesthetic preconditioning [4]. The volatile anesthetic sevoflurane is typically used in general anesthesia for patients undergoing surgery, including heart surgery [5,6]. However, the precise mechanism of sevoflurane's role in cardio-protection has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%